Simultaneous Auctions are (almost) Efficient - Feldman, Michal; Fu, Hu; Gravin, Nick; Lucier, Brendan (Symposium on Theory of Computing 2013, 2013)
Simultaneous item auctions are simple procedures for allocating items to bidders with potentially complex preferences over different item sets. In a simultaneous auction, every bidder submits bids on all items simultaneously. The allocation and prices are then resolved for each item separately, based solely on the bids submitted on that item. Such procedures occur in practice (e.g. eBay) but are not truthful. We study the efficiency of Bayesian Nash equilibrium (BNE) outcomes of simultaneous first- and second-price auctions when bidders have complement-free (a.k.a. subadditive) valuations. We show that the expected social welfare of any BNE is at least 1/2 of the optimal social welfare in the case of first-price auctions, and at least 1/4 in the case of second-price auctions. These results improve upon the previously-known logarithmic bounds, which were established by Hassidim et al. (2011) for first-price auctions and by Bhawalkar and Roughgarden (2011) for second-price auctions.